Personal black carbon exposure and its determinants among elderly adults in urban China. (May 2020) - Zhou, Huichan; Lin, Jingjing; Shen, Yu; Deng, Fuchang; Gao, Ying; Liu, Yuanyuan; Dong, Haoran; Zhang, Yingjian; Sun, Qinghua; Fang, Jianlong; Tang, Song; Wang, Yanwen; et al.
Highlight: We conducted the first investigation of personal black carbon (BC) exposure among elderly adults in urban China. The personal BC exposure level in our study is higher than those in developed countries or regions. Temperature could significantly affect personal BC exposure by affecting individual activity patterns. Individuals' education level may be a potential determinant of personal BC exposure among elderly adults. Abstract: Personal exposure to air pollution is affected by its concentration in the microenvironment and individual time-activity patterns. To investigate personal black carbon (BC) exposure levels and identify their potential determinants, we conducted a panel study among 67 elderly residents aged 60–69 years in Jinan, China. Personal BC exposure was measured using portable real-time monitors, while corresponding ambient BC concentrations and meteorological conditions were also collected from the local central site. Time-activity and household characteristics were recorded. A linear mixed-effects model was used to identify potential determinants of personal BC exposure. The daily average personal BC exposure concentration was 4.1 ± 2.0 μg/m 3 (±standard deviation, SD), which was significantly lower than the ambient concentration (4.6 ± 2.5 μg/m 3 ) ( p  < 0.001). Strong correlation ( Spearman's r =  0.63, p <  0.001) was found between personal and ambient BC concentrations. The fixed-site monitoring ambient concentration cannot fully reflect the actual personal exposure concentration. Ambient BC concentration, ambient temperature, relative humidity, education level and air purifier use were significant determinants of personal BC exposure. Our findings highlight the need for detailed assessment of personal exposure on health risk assessment of BC and also help develop strategies for targeted risk reduction.